2012
DOI: 10.1111/jdv.12057
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibiotic susceptibility patterns of Propionibacterium acnes isolated from acne patients: an Egyptian university hospital‐based study

Abstract: Propionibacterium acnes in vitro susceptibility patterns differed among Egyptian patients to the commonly prescribed antibiotics with the highest to lowest resistance to clindamycin, erythromycin, oxytetracycline, doxycycline and azithromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Generally speaking, the resistant cases mainly involved MLS B antibiotics. This high frequency of ML resistance of P. acnes in Chinese patients is consistent with the common picture throughout the world, yet the resistance rate is lower than that of the majority of western countries . This may be explained by the widespread application of macrolides (e.g.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Generally speaking, the resistant cases mainly involved MLS B antibiotics. This high frequency of ML resistance of P. acnes in Chinese patients is consistent with the common picture throughout the world, yet the resistance rate is lower than that of the majority of western countries . This may be explained by the widespread application of macrolides (e.g.…”
Section: Discussionsupporting
confidence: 84%
“…The massive and long‐term application of antibiotics makes us doubt their current potency. Numerous studies conducted throughout the world have shown that P. acnes resistance to antibiotics has become an “elephant in the room” . Nevertheless, antibiotics still remain the first‐line treatment for acne.…”
Section: Discussionmentioning
confidence: 99%
“…Erythromycin and clindamycin are often involved in cases of resistance, and there is frequent cross‐resistance to the two antibiotics . In a 2001 study performed in Singapore (Table ), these antibiotics showed the greatest percentage of resistant isolates in patients (69.2% and 50%, respectively) followed by co‐trimoxazole (38.5%) and doxycycline (23%) .…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic resistance in P. acnes is a global public health concern (Table ), and the prevalence of the problem has increased from 20% in 1978 to 62% in 1996 . The highest rates of resistance observed are against clindamycin and erythromycin …”
Section: Resultsmentioning
confidence: 99%
“…Topical and oral antibiotics are commonly used to treat acne (Gollnick et al, ; Thiboutot et al, ). Antibiotic resistance is, however, increasing, and resistance to topical macrolides reported in over 50% of P. acnes strains in many countries has decreased their effectiveness (Abdel Fattah & Darwish, ; Dreno et al, ; Gollnick et al, ; Nakase, Nakaminami, Noguchi, Nishijima, & Sasatsu, ; Nast et al, ; World Health Organization, ). Moreover, damage to stable skin microbiomes and the antibiotic resistance of nontarget bacteria as a cause of the proliferation of opportunistic pathogens are major concerns, especially in cases of Staphylococcus aureus and Methicillin‐resistant Staphylococcus aureus (Levy, Huang, Roling, Leyden, & Margolis, ; Mills Jr, Thornsberry, Cardin, Smiles, & Leyden, ; Nakase et al, ).…”
Section: Introductionmentioning
confidence: 99%